Developing adaptive systems with synchronized architectures - Seceleanu, Tiberiu; Garlan, David (The Journal of systems and software, 2006)
In this paper we show how to specify and refine self-adapting systems, by employing the state-based formalism called action systems. Assuming a fixed set of possible configurations, we use a recently-introduced synchronization operator to achieve separation of concerns between adaptation policy, fault tolerance and steady-state system execution. Using action systems allows us to apply standard refinement techniques, aimed for correct implementations of higher-level models. We illustrate this idea by applying it to the problem of coping with dynamically-varying user requirements and possible fault situations.